Computer arithmetic : algorithms and hardware implementations - Vladutiu, Mircea (Springer, 2012)
Computer Arithmetic provides a complete procedure for linking the digital design and arithmetic algorithms domain, based on original formalism and hardware description languages. Readers will find gate-level designs for all matrix/combinatorial arithmetic structures.